Psychopomp Counsel. - Evans, Chris; Zolghadr, Tirdad; De Ateliers, Amsterdam (Amsterdam : Stichting Ateliers 63, 2011)
Vunderink, Coen ; Di Massimo, Patrizio ; Räpple, Heiko ; Dordoy, Alex ; Leon, Cristobal ; Ruitenbeek, Stefan ; Visser, Jasmijn ; De Vos, Sarah ; Rhodes, Stephen ; Verboom, Marion
De Ateliers, Amsterdam, May 11 - May 22, 2011
kunstcatalogus